Motivational Interviewing Training: A Case-Based Curriculum for Preclinical Medical Students - N. Nicole Jacobs; Lisa Calvo; Aaron Dieringer; Ali Hall; Reka Danko (Association of American Medical Colleges, 2021)
Introduction With the rise of chronic medical problems involving lifestyle behaviors and the benefits of patient involvement in preventative care, medical students need to learn how to help patients change health risk behaviors and improve patient involvement in order to improve health outcomes. Motivational interviewing (MI) is a patient-centered therapeutic approach that is effective in the treatment of lifestyle behaviors and diseases. Methods This 2-hour didactic training session, along with a 3-hour case-based practice session involving role-plays and a 3-hour evaluated session utilizing standardized patients, was delivered to 68 preclinical medical students. Knowledge, attitudes, and self-efficacy were evaluated via pre- and posttraining surveys, and satisfaction with the training was assessed upon completion. Results Students who completed both pre- and postsurveys (n = 48) showed a statistically significant improvement in knowledge of MI (t = −29.73, df = 47, p < .001), attitudes regarding implementing MI in health care settings (t = −3.04, df = 47, p < .005), and self-efficacy (t = −10.699, df = 47, p < .001) in talking with patients about behavior change. Students were also highly satisfied with the MI training package (M of 4.4, SD = 0.6, out of 5.0). Discussion A training package to teach preclinical medical students about MI was effective in helping students learn the knowledge and skills necessary to deliver MI in a broad range of clinical cases.